¿Dónde están los cultivos en Argentina? Aportes del mapa Nacional de cultivos del INTA - De Abelleyra, Diego; Veron, Santiago Ramón; Banchero, Santiago; Iturralde Elortegui, Maria Del Rosario Ma; Zelaya, Daniela Karina; Murray, Francisco; Martini, Juan Pablo; Valiente, Sebastián Omar; Puig, Omar; Maidana, Daniel Agustin; Portillo, Javier Esteban; Melilli, Maria Paula; et al. (AAPRESID, 2024)
Poster